Enhancing the Lipid-Lowering Activity of Apigenin through Nanostructured Lipid Carrier (NLC) Modification - Setiawan, Fajar; Rahayuningsih, Nur; Rahma, Maya Nurul; Susilawati, Wulan Aprilia; Widyastuti, Laras Rizkia; Nurdianti, Lusi (Trends in Sciences, 2026)
A total of 2.6 million deaths and 29.7 million Disability-Adjusted Life Years (DALYs) worldwide are caused by hyperlipidemia. Apigenin is known to play a role in cholesterol regulation, but it is limited in terms of solubility and stability. Modification of Nanostructured Lipid Carriers (NLC) is known to increase the bioavailability and effectiveness of hyperlipidemia drugs. This study aims to analyze the potential of NLC drug delivery systems containing apigenin to increase antihyperlipidemia efficacy. Apigenin NLC was formulated using emulsification and melting methods. The formulation was characterized based on particle size, PDI, zeta potential, %EE, and morphology. Subsequently, in vitro release and antihyperlipidemic activity tests were conducted using the photometric method. The apigenin NLC formulation was prepared with a ratio of solid lipid to liquid lipid of 30:70 (F1), 40:60 (F2), and 50:50 (F3). The characterization results showed F3 as the optimal formula with a particle size of 172.30 ± 35.66 nm, polydispersity index of 0.57 ± 0.16, zeta potential of −26.48 ± 0.28 mV, and %EE of 77.8870 ± 0.05%. The NLC modification successfully increased apigenin release by 3-fold compared to unmodified apigenin and the activity of lowering cholesterol levels increased with a decrease in the IC50 value of apigenin’s antihyperlipidemic activity from 132.56 to 101.09 ppm in NLC-Apigenin. This study demonstrates that NLC Apigenin holds promising potential in the treatment of hyperlipidemia. HIGHLIGHTS The best of NLC-Apigenin exhibited nanoscale size (30 ± 35.66 nm), good zeta potential (−26.48 ± 0.28 mV), and high entrapment efficiency (77.8870 ± 0.05%) Nanostructured Lipid Carrier (NLC) enhanced apigenin release up to 3-fold compared to unmodified apigenin. NLC-Apigenin reduced the IC50 value from 132.56 to 101.09 ppm, confirming improved lipid-lowering activity. GRAPHICAL ABSTRACT